Análise da influência do escore de condição corporal e de diferentes concentrações de parições nos índices reprodutivos de vacas de corte através de simulação - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Cattle breeding is one of the main agricultural activities developed in the country, representing 6% of Brazilian PIB and 30% of agribusiness PIB. For this productive chain to provide good economic returns, reproductive performance is one of the main factors to consider, so that the females come to conceive a calf a year for the producer. The objective of this study was to analyze, through a simulation model of the reproductive performance of females, the influence of the condition score body weight (ECC) at birth and concentration of parturition, at conception rates, on the date of the next calving, in the calving-conception interval and in the calving interval. The work was carried out from a performance simulation model females, and to obtain the results, 10 simulations for each CC score, being 100 animals per simulation. The herd was composed of females with ECC 2, 3 and 4, being tested two scenarios, one with childbirths defined as precocious and the other late. With the obtained results it can be observed that the ECC has great influence on the analyzed reproductive indices. For the scenario with early parities, mean values of IEP de 397,87 days for ECC 2, 374,16 days for ECC 3 e 366,13 days for ECC 4. For the IPC, mean values were 116.75 days for ECC 2, 92.19 days for ECC 3, and 84.34 days for ECC 4. At rates in conception were 100% for EEC 3 and 4 and 90% for ECC2. In the scenario with late parisons were found rates in conception low for the categories of ECC 2, and for the average IEP of 392 days for ECC 2, 365.46 days for ECC 3 and 359.4 days for ECC 4, for IPC averages of 117.79 days for ECC 2, 89.61 days for ECC 3, and 78.45 days for ECC 4. This shows the importance of adopting good food management for females during the pre and postpartum period, and that it is important for females to have ECC appropriate for calving and during the breeding season. In addition, it is observed the importance of the concentration of deliveries at the beginning of the calving season, as this allows good conception rates for wombs with low body score at birth.
Keywords: Bovinocultura de corte; Condição nutricional; Modelagem; Cattle breeding; Modeling; Nutritional condition; CNPQ::CIENCIAS AGRARIAS